Hak Kreditur Pemegang Jaminan pada Perseroan Terbatas yang Dinyatakan Pailit - Efraint Pangondian Sinaga; Nadia Maulisa (SIGn Jurnal Hukum, 2022)
This study aims to analyze and explain the position of creditors as holders of the pledge of shares of a Limited Liability Company declared bankrupt. This study also aims to determine the legal remedies creditors can take if they experience these problems. This study uses a normative juridical research method with a statute and conceptual approach. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal materials are then analyzed using qualitative data analysis methods. The results show that the position of creditors as holders of the pledge of shares of a Limited Liability Company declared bankrupt is preferred creditors. However, the position of creditors will mutatis mutandis change from preferred creditors to concurrent creditors because the collateral object no longer exists. In addition, creditors can make efforts as holders of the pledge of shares related to Limited Liability Company declared bankrupt, namely preventive and repressive efforts. However, repressive efforts are insufficient to provide justice, certainty, and legal protection to creditors as holders of the pledge of shares. Therefore, it is recommended to creditors as holders of the pledge of shares to make preventive efforts: authentic deed, authorization letter to sell the collateral object, adding another collateral object, and auditing prospective debtors and collateral objects. In addition, it is recommended for the Government to harmonize and regulate several applicable laws and regulations regarding the pledge of shares. In this case, creditors as holders of the pledge of shares have more power, certainty, and legal protection in the pledge of shares agreement in the future.